2022
DOI: 10.21203/rs.3.rs-1900171/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the 99DOTS digital adherence technology on tuberculosis treatment outcomes in North India: a pre-post study

Abstract: Background: 99DOTS is a cellphone-based digital adherence technology. The state of Himachal Pradesh, India, made 99DOTS available to all adult patients with drug-sensitive tuberculosis (TB) in May 2018. While 99DOTS has engaged over 300,000 patients across India, few studies have evaluated its impact on TB treatment outcomes. Methods: We compared treatment outcomes of adult patients with drug-sensitive TB before and after Himachal Pradesh’s 99DOTS launch using data from India’s national TB database. Pre-interv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
2
6
0
1
Order By: Relevance
“…The 57.7% of overall doses confirmed by phone calls in our study is similar to that reported in two studies from India and a meta-analysis which included this study and 10 other DAT implementation projects. (7, 8) In addition, the decreased engagement over the course of treatment is similar to that reported in India by Cross et al(2) However, through a combination of self-report and calls to people with TB, health workers confirmed that >98% of expected doses were taken. Thomas et al also confirmed high levels of adherence (88%) among people with TB using 99DOTS in India using random urine isoniazid screening.…”
Section: Discussionsupporting
confidence: 78%
“…The 57.7% of overall doses confirmed by phone calls in our study is similar to that reported in two studies from India and a meta-analysis which included this study and 10 other DAT implementation projects. (7, 8) In addition, the decreased engagement over the course of treatment is similar to that reported in India by Cross et al(2) However, through a combination of self-report and calls to people with TB, health workers confirmed that >98% of expected doses were taken. Thomas et al also confirmed high levels of adherence (88%) among people with TB using 99DOTS in India using random urine isoniazid screening.…”
Section: Discussionsupporting
confidence: 78%
“…In the only randomized trial of 99DOTS to date, we showed that only 52% of people with TB were enrolled on 99DOTS, and 99DOTS-based treatment supervision did not improve treatment outcomes (2). Other implementation studies have found similarly low enrollment of people with TB on 99DOTS and have reported similar treatment outcomes between routine- and 99DOTS-based treatment supervision (1-3).…”
Section: Introductionmentioning
confidence: 82%
“…Digital adherence technologies (DATs) have been proposed as one potential intervention to support people with TB to successfully complete treatment. 99DOTS is a low-cost DAT, whereby people with TB self-report medication dosing by calling toll-free phone numbers hidden underneath pills in blister packs (1,2). 99DOTS has been deployed in some Asian and African countries, including India (1,3), Uganda (2) and Kenya (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil lain yang berbeda ditunjukan oleh Chen et al (2022) di India, hasil penelitian ini menunjukkan bahwa tidak ada perbedaan yang signifikan dari hasil kepatuhan pengobatan sebelum dan sesudah implementasi 99DOTS. Didukung dengan penlitian Thomas et al (2019) di India, dimana penilaian 99DOTS memberi hasil yang kurang optimal dalam mengukur kepatuhan, sebagian dikarenakan kurangnya keterlibatan pasien pada 99DOTS.…”
Section: Intervensi Menggunakan Aplikasi Digital 99dotsunclassified